Polysubstituted pyrrole derivatives via 1,2-alkenyl migration of novel γ-amino-α,β-unsaturated aldehydes and α-diazocarbonyls - Cai, Shuting (2016)
Tri-substituted pyrrole derivatives were successfully synthesized from aminoaldehyde and α-diazocarbonyl, using a TiCl4 catalyst. The reactions proceeded via 1,2-migration and condensation, leading to the corresponding pyrroles in moderate to excellent yields. Reaction susceptibility was subsequently demonstrated by the variation in substrates.